Description of Anxiety Level And Characteristics of Pregnant Mothers During COVID-19 Pandemic - R OKTAVIANCE SIMORANGKIR; Merlina Sinabariba; Aprilita Br Sitepu; Angelina Agatha Br Sembiring (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
Abstract The COVID-19 pandemic that has lasted for two years has actually caused anxiety disorders for pregnant women. Pregnant women who are positive for COVID-19 are also at higher risk for pregnancy complications. To find out the description of the level of anxiety and characteristics of pregnant women during the COVID-19 pandemic at the Talia Pratama Clinic in 2022. The sampling technique is Total Sampling with 50 respondents. Research results based on anxiety almost all experienced severe anxiety (58%), based on high school education (34%), based on farmer occupation (38%), based on age 20-35 years old (98%), based on income IDR 1.5 million 2 million (72%), based on multigravida parity (84%). Conclusion The level of characteristics of pregnant women has a very important distribution in influencing the level of anxiety of pregnant women in the future pandemic COVID-19